Electrophysiological and behavioral response of red palm weevil, Rhynchophorus ferrugineus (Olivier) (Coleoptera: Dryophthoridae) to fermented coconut sap neera - Venugopal, Vibina; Subaharan, Kesavan (Journal of Plantation Crops, 2019)
Red palm weevil (RPW) (Coleoptera: Curculionidae) is a lethal pest of coconut in India and various palms across the world. Fermenting toddy has been traditionally used for trapping RPW. The traditional method of collecting neera, the coconut inflorescent sap, in an open earthen pot emanates volatiles that attract these insects. In this study, the volatile compounds released from fermenting neera were characterized and the compounds that cause physiological and behavioral response to RPW were established using electrophysiological and behavioural assays. Acetoin, which caused the neuronal response in adult RPW antennae, was present in head space volatiles of fermenting neera from day one onwards. Fermenting neera, when used in tandem with aggregation pheromone, trapped a high number of weevils (53.2 per trap) suggesting possibilities of its use in RPW management.